Impact of Lhcx2 on Acclimation to Low Iron Conditions in the Diatom Phaeodactylum tricornutum - Buck, Jochen M.; Wünsch, Marie; Schober, Alexander F.; Kroth, Peter G.; Lepetit, Bernard (Frontiers in Plant Science, 2022)
Iron is a cofactor of photosystems and electron carriers in the photosynthetic electron transport chain. Low concentrations of dissolved iron is therefore the predominant factor that limits growth of phototrophs in large parts of the open sea like the Southern Ocean and the North Pacific, resulting in “High nutrient – low chlorophyll” (HNLC) areas. Diatoms are among the most abundant microalgae in HNLC zones. Besides efficient iron uptake mechanisms, efficient photoprotection might be one of the key traits enabling them to outcompete other algae in HNLC regions. In diatoms, Lhcx proteins play a crucial role in one of the main photoprotective mechanisms, the energy-dependent fluorescence quenching (qE). The expression of Lhcx proteins is strongly influenced by various environmental triggers. We show that Lhcx2 responds specifically and in a very sensitive manner to iron limitation in the diatom Phaeodactylum tricornutum, on the same timescale as the known iron regulated genes ISIP1 and CCHH11. By comparing Lhcx2 knockout lines with wild type cells, we reveal that a strongly increased qE under iron limitation is based on the up-regulation of Lhcx2. Other observed iron acclimation phenotypes in P. tricornutum include a massively reduced chlorophyll a content/cell, a changed ratio of light harvesting and photoprotective pigments per chlorophyll a, a decreased amount of photosystem II and photosystem I cores, an increased functional photosystem II absorption cross section, and decoupled antennae complexes. H2O2 formation at photosystem I induced by high light is reduced in iron-limited cells, while the amount of total reactive oxygen species is rather increased. Our data indicate a possible reduction of total oxidative stress by Lhcx2 based qE, while the other iron acclimation phenotype parameters monitored are not affected by the amount of Lhcx2 and qE.